2017
DOI: 10.1162/jocn_a_01120
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Chunking in Derived Words: A Parametric fMRI Study

Abstract: In usage-based linguistic theories, the assumption that high-frequency language strings are mentally represented as unitary chunks has been invoked to account for a wide range of phenomena. However, neurocognitive evidence in support of this assumption is still lacking. In line with Gestalt psychological assumptions, we propose that a language string qualifies as a chunk if the following two conditions are simultaneously satisfied: The perception of the whole string does not involve strong activation of its in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 59 publications
1
25
0
Order By: Relevance
“…In a similar vein, it is widely acknowledged that predictions play a role at all levels of language understanding (Kuperberg & Jaeger, ). At the morphological level, a masked visual priming experiment found that lexical decision times to complex words (e.g., tearless , worthless ) correlate with surprisal for the suffix (− less ), given the base ( tear , worth ) (Blumenthal‐Dramé et al, ). In this experiment, native speakers of English had to decide, as quickly and accurately as possible, whether a string of letters was a possible word of English, after brief (60 ms) exposure to the first morpheme of the word (e.g., worth—WORTHLESS , ticket—TICKETMENT ).…”
Section: Multiscale Predictive Processing Across Domainsmentioning
confidence: 99%
“…In a similar vein, it is widely acknowledged that predictions play a role at all levels of language understanding (Kuperberg & Jaeger, ). At the morphological level, a masked visual priming experiment found that lexical decision times to complex words (e.g., tearless , worthless ) correlate with surprisal for the suffix (− less ), given the base ( tear , worth ) (Blumenthal‐Dramé et al, ). In this experiment, native speakers of English had to decide, as quickly and accurately as possible, whether a string of letters was a possible word of English, after brief (60 ms) exposure to the first morpheme of the word (e.g., worth—WORTHLESS , ticket—TICKETMENT ).…”
Section: Multiscale Predictive Processing Across Domainsmentioning
confidence: 99%
“…Following Baayen (2002, 2005), we consider morphological boundary strength to be a gradient property of morphological boundaries reflecting their salience and the degree of segmentability of complex forms (Hay & Baayen, 2002. On this view, boundary strength is influenced by multiple parameters such as morphological productivity, semantic transparency, and the relative frequency of base and derived word (Blumenthal-Dramé et al, 2017;Hay & Baayen, 2002;Vannest, Newport, Newman, & Bavelier, 2011). The gradience of morphological boundaries, and the consequences of segmentability for the representation of words and morphemes, are a matter of active debate (Baayen, 2014;Hay & Baayen, 2005).…”
mentioning
confidence: 99%
“…These are processed bilaterally in 'language regions', with varying contribution of the left and right hemisphere as a function of, among other things, familiarity [139][140][141][142][143][144][145] . Furthermore, the more familiar [146][147][148][149][150][151][152] , frequent [153][154][155][156][157] , compositional ('red boat' vs 'cup boat') or coherent multiword expressions are 158,159 , the less 'language regions' tend to be active. Some studies show that sensorimotor activity is more strongly associated with high frequency words, word composition and impairments of word composition 160,161 while the basal ganglia are less active for higher frequency words 157,162 .…”
Section: Comprehensionmentioning
confidence: 99%
“…Furthermore, the more familiar [146][147][148][149][150][151][152] , frequent [153][154][155][156][157] , compositional ('red boat' vs 'cup boat') or coherent multiword expressions are 158,159 , the less 'language regions' tend to be active. Some studies show that sensorimotor activity is more strongly associated with high frequency words, word composition and impairments of word composition 160,161 while the basal ganglia are less active for higher frequency words 157,162 . One study concluded that 'areas canonically implicated in traditional neurophysiological models of language processing appear to play a lesser role in basic composition' (p. 2802) 160 .…”
Section: Comprehensionmentioning
confidence: 99%